Conditioning monitoring of train system from sub-systems to predictive fault detection - Zhu, Yukai (Nanyang Technological University, 2023)
This Final Year Project (FYP) aims to explore the possibility of carrying out predictive analysis to predict potential train faults for Singapore Mass Rapid Transport (MRT) from the available data provided. The primary objective of this project is to determine valuable indicators within the available data that can be utilized as performance metrics for the purpose of predictive analysis on MRT trains in Singapore.